2017
DOI: 10.1007/s40495-017-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Infection: a Cause of and Cure for Cancer

Abstract: Purpose of ReviewThis article provides a brief overview of the role that infections play in cancer emergence and cancer treatment.Recent FindingsA select number of pathogens have been reported to increase the incidence of specific cancers (directly through altering gene expression or indirectly through inducing chronic inflammation). These have been referred to as oncogenic pathogens. Conversely, a subset of pathogens has been demonstrated to preferentially cause lysis of tumor cells, leading to tumor regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…and Patients with Tumors in the Lung. Reports describing cancer outcomes in the context of infection have been discordant (18)(19)(20)(21). We recently reported that active influenza virus infection in the lung accelerates early melanoma growth in the skin (22).…”
Section: Active Influenza Virus Infection In the Lung Improves Outcommentioning
confidence: 99%
“…and Patients with Tumors in the Lung. Reports describing cancer outcomes in the context of infection have been discordant (18)(19)(20)(21). We recently reported that active influenza virus infection in the lung accelerates early melanoma growth in the skin (22).…”
Section: Active Influenza Virus Infection In the Lung Improves Outcommentioning
confidence: 99%
“…Cancer emerges from the transformation of normal cells into tumor cells in multiple stages, i.e., carcinogenesis/tumorigenesis or oncogenesis, that usually arises from a pre-cancerous lesion to a malignant tumor [103,104]. It has now become the leading cause of death in all age groups due to several factors, including exposure to certain radiations [105] and carcinogenic chemicals [106], infection by bio-carcinogens (e.g., certain bacteria, viruses, or parasites) [107], aging, genetic factors, geographic location, and improper and/or unhealthy diet [108,109].…”
Section: Gqd-based Electrochemical Immunosensors For Cancer Diagnosismentioning
confidence: 99%
“…Pattern-associated molecular patterns (PAMPs), including vDNA, as well as damage-associated molecular patterns (DAMPs) from cell lysis, trigger the IL-2 signaling pathway, resulting in the dispatch of CD4+ and CD8+ cytotoxic T cells, effectively attacking the cancer. Further release of alert cytokines, including TNF-and other interleukin molecules, results in stimulation of innate immune responses; with subsequent downregulation of MHC-1 production, further activation of innate and adaptive host immunity results in effective destruction of malignant cells and viral material [38].…”
Section: "Duet": Oncolytic Virotherapymentioning
confidence: 99%